Household Destroyed Due to Husband's Brother's Intervention - Al Manar, Irwansyah; Thabrani, Abdul Mukhti; Yaqin, Nurul (Borong Newinera Publisher, 2025)
Marital relationships are always related to harmony and balance is an important cornerstone. However, often, interference from third parties can become a problem that damages and threatens the stability of a household. This study aims to explore the detrimental effects of such interference on marital stability, emphasizing the importance of communication, boundaries, and mutual respect in marital relationships to overcome challenges within the household. This research uses a qualitative approach. Based on the researchers' findings, one of the common causes of marital breakdown is interference from the husband's relatives or family who are too dominant in the couple's household affairs. The role of the husband's siblings, be they younger siblings, parents, or even extended family, is often an important question in marriage dynamics.